The Relationship Between Stress Levels and Physical Activity and the Incidence of Primary Dysmenorrhea in Female Students - Khoirunnisa' Ayu Styaningrum; Rosyidah Alfitri; Anik Purwati (Health Dynamics, 2025)
Background: The presence of abdominal cramps during menstruation defines dysmenorrhea. Dysmenorrhea is caused by increased levels of prostaglandin (PG) F2-α, which belongs to the category of cyclooxygenase (COX-2) enzymes. Dysmenorrhea causes psychological impact in the form of anxiety and stress and physical impact in the form of impaired physical activity. To reduce these negative effects, the role of midwives as educators is very important. The objective of this study was to evaluate the association between reported stress levels, physical activity engagement, and the incidence of primary dysmenorrhea among female students at Sunan Kalijogo High School in the Jabung District of Malang Regency. Methods: The method used by researchers is quantitative with a correlational analysis design. This research design uses cross-sectional approach and bivariate analysis with the Spearman Rank test. This study employed probability sampling, specifically using the cluster sampling technique. Results: The analysis yielded a p-value (Sig. 2-Tailed) of 0.012 for stress levels in relation to the incidence of primary dysmenorrhea, indicating a highly statistically significant relationship. The analysis produced a two-tailed p-value of 0.025 for physical activity and dysmenorrhea, indicating a statistically significant association between these variables, as this value is below the 0.05 threshold. Conclusion: Dysmenorrhea will increase pain because a lack of physical activity can inhibit blood and oxygen circulation, which can inhibit the production of endorphins. This can cause stress, which has an impact on increasing the incidence of primary dysmenorrhea. When stressed, the body produces excessive estrogen and prostaglandin hormones that cause an excessive increase in uterine contractions, leading to pain during menstruation.